Length-weight relationships for the fifty littoral and coastal marine fish species from the Eastern Adriatic Sea - Soldo, Alen (Array, 2020)
The length–weight relationship parameters are reported for the fifty littoral and coastal marine fish species from the Eastern Adriatic. Captures were made between the years 2004 and 2017 during sport fishing competitions. The parameters a and b of the equation W = aLb were estimated. The b values ranged from 2.1972 for Spicara smaris (Linnaeus, 1758) to 3.7044 for Salaria pavo (Risso, 1810). The L-W relation for Scyliorhinus stellaris (Linnaeus, 1758), Gobius bucchichi Steindachner 1870, Gobius geniporus Valenciennes 1837 and Lipophrys trigloides (Valenciennes, 1836) are not available in FishBase and presents new data for these species. For some other species, such as Labrus mixtus Linnaeus 1758, there are only two relationships, but none from the Mediterranean, for Gobius paganellus Linnaeus 1758 only four relationships and none from Central and Eastern Mediterranean, while for Labrus merula Linnaeus 1758, Symphodus mediterraneus (Linnaeus, 1758), Symphodus roissali (Risso, 1810), Gobius cobitis Pallas 1814, Gobius cruentatus Gmelin 1789, Gobius niger Linnaeus 1758, Parablennius gatorugine (Linnaeus, 1758), Parablennius sanguinolentus (Pallas, 1814), Salaria pavo (Risso, 1810), and Bothus podas (Delaroche, 1809) very low number of relationships are presented and none from the Adriatic Sea.